Citizen Science as a Co-Creative Measure to Water Quality: Chemical Data and Local Participation in a Rural Territory - Yevenes, Mariela A.; Pereira, Helen; Bermudez, Rafael (Frontiers in Environmental Science, 2022)
It is becoming increasingly clear that the threat to the use of natural landscapes and persistent droughts are affecting the water quality of rural communities. The socio-ecological fit emerges as an aid to advance in the search for solutions to environmental problems in rural communities. Consequently, between May 2016 and September 2021, an interdisciplinary study of community-based water quality monitoring (CWQM) was implemented at a coastal catchment in the Ñuble region, Central Chile. The objective of the study was to involve the participation of local communities in initiatives to control the water quality of various parameters [pH, total iron (FeT), alkalinity as CaCO3, hardness (Ca2+ and Mg2+), sodium (Na+) and potassium (K+), water temperature, sulfate (SO42−) chloride (Cl−), and nitrate (NO3-)] in groundwater, share local knowledge, and apply co-creative measures for improving water conservation. In situ chemical data were also analyzed in the laboratory to check data quality. The PHREEQC hydrogeochemical model is used to characterize hydrogeochemical parameters of groundwater and to know about hydrogeochemical processes related to water quality. High levels of NO3− and FeT are recorded in 75% of the groundwater samples, mainly when water scarcity is higher during the summer. According to Chilean standards, nitrate levels exceed the maximum permissible limits for drinking water. A type of mainly Ca (Mg)–HCO3− carbonated water was recorded with Ca2+, Na+, Mg2+, and HCO3− as dominant ions. This study demonstrated the opportunity of a rural community group to help fill spatial data gaps in water quality monitoring and reassess water quality protection, especially considering the decrease in water availability in the region. Therefore, the community together with researchers can respond with an early alert system to water quality to collaborate with the implementation of rural drinking established on a community-based water quality monitoring. Moreover, to prioritize the level of urgency of rural water, minimize water pollution and improve the perception of the water and the resilience of their social–ecological system.